A novel submaximal field test of fatigue resistance in professional cyclists - Martinez-Gonzalez, B.; Giorgi, A.; Marcora, S. M. (Journal of Science and Cycling, 2023)
Induced by a given amount of prior accumulated work, it should be possible to quantify fatigue resistance by measuring changes in perception of effort, not requiring a maximal effort from the athletes. The aim of the study was to investigate the impact of prior accumulated work on perception of effort during submaximal exercise in professional cyclists. Seven male professional cyclists performed a submaximal field test consisting of three 5-minute bouts at three different power outputs in both fresh and fatigued states. Heart rate (HR), ratings of perceived exertion (RPE), and power output (PO) data were collected. Before the submaximal test in the fatigued state total work done was 3244 ± 83 kJ. RPE and HR were higher in the fatigued state than in the fresh state (p < 0.05). Absolute and relative PO during the submaximal test were not different between fresh and fatigued states (p > 0.05). The main findings of the study are that both RPE and HR during submaximal exercise are sensitive indicators of the state of fatigue induced by more than 3000 kJ of work done in professional cyclists. Therefore, we proposed a feasible submaximal exercise protocol to test fatigue resistance in the field.